The Role of Chemokines in Shaping the Balance Between CD4+ T Cell Subsets and Its Therapeutic Implications in Autoimmune and Cancer Diseases - Karin, Nathan; Wildbaum, Gizi (Frontiers in Immunology, 2015)
Chemokines are the key activators of adhesion molecule and also drivers of leukocyte migration to inflammatory sites and are therefore mostly considered as proinflammatory mediators. Many studies, including ours, imply that targeting the function of several key chemokines, but not many others, could effectively suppress inflammatory responses and inflammatory autoimmunity. Along with this, a single chemokine named CXCL10 could be used to induce antitumor immunity, and thereby suppress myeloma. Our working hypothesis is that some chemokines differ from others as aside from being chemoattractants for leukocytes and effective activators of adhesion receptors that possess additional biological properties making them “driver chemokines.” We came up with this notion when studying the interlay between CXCR4 and CXCL12 and between CXCR3 and its three ligands: CXCL9, CXCL10, and CXCL11. The current mini-review focuses on these ligands and their biological properties. First, we elaborate the role of cytokines in directing the polarization of effector and regulatory T cell subset and the plasticity of this process. Then, we extend this notion to chemokines while focusing on CXCL 12 and the CXCR3 ligands. Finally, we elaborate the potential clinical implications of these studies for therapy of autoimmunity, graft-versus-host disease, and cancer.